Joop W. de Wit. Poverty, Policy and Politics in Madras Slums: Dynamics of Survival, Gender, and Leadership. New Delhi: Sage Publications. 1996. 305 pages. Hardbound. Indian Rs 395.00. (The Pakistan Development Review, 1996)
The urban bias in economic development, coupled with the modernisation in agriculture and resultant labour displacement, has meant that the growth rates of the urban population have far outstripped the rapidly rising overall population growth rates in developing countries. Employment generation in the urban sectors generally does not keep pace with the growth in urban populations. Lack of access to education and training leads to low skill formation. A growing number of urban people are, therefore, forced to work in the informal sector. Low and uncertain incomes and the lack of suitable housing forces these people to reside in sub-human conditions without basic sanitation and health services. In recent years, the urban slum has become an increasing focus of economic development analyses and policy-making.